The instant decorator - Gold, Frances Joslin (New York : Clarkson Potter Publishers, 1976)
The Instant Decorator is a new kind of decorating book that fills a space left open in spite of the infinite number of books on the subject. The Instant Decorator lets you ' 'do your own thing" and select fabrics, colors, and styles that reflect your own taste. This visual-aid book will be an aid in making choices and avoiding costly mistakes that often occur when trying to make non-visual decorating decisions. Your own ideas and preferences, as thought out and worked out in this new workbook, will serve as a guide and will also help you in communicating with an interior designer if you feel that you need professional expertise. This book is designed as a visual aid for the home decorator. In setting out to decorate or redecorate a room, most of us spend a great deal of time looking for ideas and inspiration. Without decorating know-how we tend to become confused by the abundance of choices. We decide on a basic plan and begin to assemble samples of fabrics, carpeting, and paint colors, we bring them home to see how they will look in a room, but after all our effort, often find ourselves more frustrated than decisive. We cannot visualize the effect we hope to achieve by looking at small samples and swatches in an actual room. The main purpose of The Instant Decorator is to enable you to experiment with different decorating ideas and to plan all your colors, fabrics, textures, and furnishings before making any purchases. The Instant Decorator includes basic information for those who do not have the time to learn about decorating in depth but need a quick reference source.
Foreword -- Introduction -- How to use this book -- Sixteen see-through rooms -- Planning -- Furniture arrangement -- Color -- Fabrics -- Walls and wall coverings -- Floor coverings -- Windows -- Lighting -- Accessories -- Art in your home -- A guide to furniture styles.
Keywords: INTERIOR DECORATION -- HANDBOOKS, MANUALS, ETC